Evaluasi Manajemen Event Gelar Melayu Serumpun Kota Medan, Sumatera Utara - Adillah Falisa Dilmy; Apriliani Lase (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to evaluate the management of the Gelar Melayu Serumpun Event held in Medan City, North Sumatra, as part of an effort to preserve Malay culture and improve local tourism. This study uses a descriptive qualitative approach with a case study method by adapting Golbalt's theory. Purposive sampling technique was used to select relevant informants, including two members of the Tourism Office, one person from the event organizer, one member of the native Malay community, and one visitor. Data were collected through in-depth interviews, direct observation, and documentation analysis. The results of the study indicate that cross-agency coordination, especially between the Tourism Office and the event organizer, went well, especially in terms of technical planning and more innovative stage design compared to the previous year. However, there were several weaknesses such as limited facilities for visitors and less than optimal booth arrangement in displaying Malay culture. Nevertheless, this event was considered successful in promoting Malay cultural identity to local and international communities and increasing participation from delegations from related countries. This evaluation provides several recommendations for future improvements, especially in terms of improving visitor facilities and mitigating weather-related risks. With better planning, Gelar Melayu Serumpun has great potential to become a sustainable cultural event and can further support the development of Medan City's tourism sector.